Faktor Faktor Yang Mempengaruhi Prestasi Kerja Pegawai Kementrian Perhubungan Laut Distrik Navigasi Kelas I Palembang - Nugraha, Erlangga Dwi; Rismansyah, Rismansyah; Hendri, Edduar (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to test empirically the effect of work design,work environment on employee performance at the Class I Navigation District Office in Palembang. Factorc influencing work performance of employees of the ministry of transportation marine Navigation Class I District Palembang. In this study the type of data used was primary data and the method used was quatitative method, the data collection technique used was documentation, questionnaires. The population in this study were127 employees of the maritime transportation office of the Navigation District of Class I Palembang and the sampling technique used in this research was saturated sample, the research data were analyzed using multiple regression SPSS program software. Analysis of the data used in this study using multiple linear regression analysis, correlation coefficient analysis and determination coefficient analysis. The hypothesis test used is the t test f test.